Ceramic on ceramic total hip arthroplasty and liner fracture. Two case reports and review of literature - Goretti, Claudio; Polidoro, Federico; Paderni, Stefania; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Ceramic on ceramic bearing surfaces in total hip arthroplasty are rising in number with the purpose of reducing debris osteolysis in young patients. New generation ceramics drastically reduced the well known problem of liner’s fracture associated with this material but this still represents a complication. Methods: We present the only two cases of acetabular liner fracture we had in our department, on a total of 252 patients, since we use CoC bearing surfaces in THR (2005-2019) analyzing symptoms and causes of this complication. Review of recent literature focused on symptoms and causes of liners fracture, well matched our cases. Results: In line with the analysis of literature, the major cause of liner fracture is neck-cup impingement resulting in the “edge-loading” effect, followed by other factors like prosthesis design, traumas and patient weight. From data also emerge the role of acoustic phenomena (e.g. squeaking) and CT scan in the diagnostic process. Conclusions: Last generation ceramics should be used in CoC THR, implant malposition and prosthesis design have a dominant role in liner fracture, squeaking should always be investigated. CT scan have an important role in diagnosis. Implant revision with substitution of the bearing surfaces is mandatory in case of fracture or impending fracture signs.